Integration of functional programming and spatial databases for GIS application development - Sérgio Souza Costa (2006)
Recently, researchers in GIScience argued about the benefits on using functional programming for geospatial application development and prototyping of novel ideas. However, developing an entire GIS in a functional language is not feasible. Support for spatial databases requires a large set of I/O operations, which are cumbersome to implement in functional languages. This thesis presents an application that interfaces a functional language with a spatial database. It enables developing GIS applications development in a functional language, while handling data in a spatial database. We used this application to develop a Map Algebra, which shows the benefits on using this paradigm in GIScience. Our work shows there are many gains in using a functional language, especially Haskell, to write concise and expressive GIS applications. Combining Haskell and TerraLib enables the use of functional programming to reallife GIS problems, and is a contribution to make Haskell a more widely used tool for GIS application development.